Reproduction and establishment of two endangered African cedars, Widdringtonia cedarbergensis and Widdringtonia whytei - Mitrani, Leila Mical (Department of Biological Sciences, 2017)
In this thesis I determine the effect of population decline on reproduction for two critically endangered African cedars. Widdringtonia whytei (Mulanje cedar) endemic to Mt Mulanje, in Malawi and Widdringtonia cedarbergensis (Clanwilliam cedar) endemic to the Cedarberg Mountains in the Western Cape Province of South Africa. Populations of both species have declined dramatically in the recent past and both show evidence of insufficient recruitment. Recent research has shown that a reduction in population density may limit pollen dispersal, reduce seed viability and increase self-pollination rates, causing an inbreeding depression, resulting in less fit offspring. Based on this research, I hypothesise that pollen transfer in Widdringtonia is distance-dependant and therefore populations with greater distances to the nearest adult neighbour will have lower seed viability, due to pollination failure. I also hypothesise, that trees which receive less outcross pollen due to distance-dependant pollination will have higher rates of self-pollination. I further hypothesise that seed viability may also increase with increased soil nutrients and more amenable climate differences linked to changes in altitude. To test these hypotheses, I determine the extent to which reduced population density has resulted in a decline in viable seed using germination experiments, followed by cut tests and tetrazolium chloride tests. For W. cedarbergensis seedling survival was determined in a greenhouse and self-pollination was assessed with ISSR markers, using DNA extracted from parent and offspring. My results show that seed viability for both W. cedarbergensis and W. whytei is not significantly correlated with distance to nearest-neighbour, altitude or soil nitrogen, carbon or phosphorus. These results suggest that current population densities are not effecting the reproduction either of W. whytei or W. cedarbergensis. My results for population genetics show relatively low levels of genetic variation in W. cedarbergensis typical of endangered and endemic species. The genetic differentiation between populations is low, suggesting that pollen flow between populations is adequate and populations are not genetically isolated. I conclude that there is no evidence that population decline is causing any noticeable limitations on pollen transfer and reproduction in Widdringtonia.